Peran Guru BK Dalam Menangani Perilaku Membolos di SMAN 8 Kota Cirebon - Thayibatunisa, As Syifa Sidikah; Deratian Prima Aulia Putri Khusayu; Ganis Ainnur Rahma; Vany Dwi Putri (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This research aims to deal with educational problems, namely truant behavior, the method used is a qualitative method with the type of observation at SMAN 8 Cirebon City school. Observation is a strategy for obtaining information by direct observation. Truant behavior is a deviant act which, if left unchecked, will hamper the success of an education, truancy or absence without permission has become commonplace now. In America, absenteeism is considered a problematic issue. This is because according to several studies, truant behavior is considered a predictor of juvenile delinquency. This truant behavior occurs due to two factors, namely internal factors and external factors, one example of which is the low level of student motivation, and problems in the community or family environment experienced by students. Here the role of the Guidance Teacher is needed to provide solutions and motivation, as well as appropriate direction in providing the approaches and techniques that students need.